Chebyshev polynomial practice: medium sum

Geometry Level 3

Evaluate

k = 1 45 csc 2 ( 2 k 1 ) \displaystyle \sum_{k=1}^{45} \csc^2(2k-1)

The angle is given in degrees.


The answer is 4050.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Trevor Arashiro
Apr 13, 2015

I'll post a full solution tomorrow, too tired rn.

For now, note that 1 45 csc 2 ( 2 k 1 ) = 1 45 sec 2 ( 2 k 1 ) \displaystyle \sum_1^{45} \csc^2(2k-1)=\displaystyle \sum_1^{45} \sec^2(2k-1)

And that when you reverse the coefficients of f ( x ) f(x) that the roots become inverted (eg: if the roots of f ( x ) f(x) are a , b , c a,b,c then when the coefficients are reversed, the new polynomial has roots 1 a , 1 b , 1 c \frac{1}{a},~\frac{1}{b},~\frac{1}{c} )

Also, we are once again working with T 90 ( x ) T_{90}(\sqrt x)

Moderator note:

Your solution is insufficient and barely contain any relevant working. You should also clarify that the angles are in degrees. Note that we assume angles are in radian unless stated as otherwise (like inserting the degree symbol: ^\circ ).

Matt Janko
May 6, 2020

Let a a be a positive integer. There is a fairly well-known identity, which we will prove below: k = 1 a 1 csc 2 k π a = a 2 1 3 . (1) \sum_{k = 1}^{a - 1} \csc^2 \frac {k\pi}a = \frac {a^2 - 1}3. \tag{1} In words, this identity gives the sum the square cosecants of all the integer multiples of π / a \pi/a in the first two quadrants. We are interested in the sum of the square cosecants of the odd integer multiples of 1 = π / 180 1^\circ = \pi/180 in the first quadrant, so we can find the sum of all the integer multiples in the first two quadrants, subtract the sum of the even integer multiples, and divide by 2: k = 1 45 csc 2 ( ( 2 k 1 ) π 180 ) = 1 2 ( k = 1 179 csc 2 k π 180 k = 1 89 csc 2 2 k π 180 ) = 1 2 ( 18 0 2 1 3 9 0 2 1 3 ) = 4050 . \sum_{k = 1}^{45} \csc^2 \left( \frac {(2k - 1)\pi}{180} \right) = \frac 12 \left( \sum_{k = 1}^{179} \csc^2 \frac {k\pi}{180} - \sum_{k = 1}^{89} \csc^2 \frac {2k\pi}{180} \right) = \frac 12 \left( \frac {180^2 - 1}3 - \frac {90^2 - 1}3 \right) = \boxed{4050}.

Now let us prove (1). For brevity, put ω k = sin 2 ( k π / a ) \omega_k = \sin^2 (k\pi/a) . Let P a P_a denote the polynomial defined by P a ( x ) = k = 1 a 1 ( x ω k ) , P_a(x) = \prod_{k = 1}^{a - 1}(x - \omega_k), and let r a r_a and s a s_a denote the constant and linear coefficient of P a P_a . By Vieta, k = 1 a 1 csc 2 k π a = k = 1 a 1 1 ω k = k j k ω j k ω k = s a r a . \sum_{k = 1}^{a - 1} \csc^2 \frac {k\pi}a = \sum_{k = 1}^{a - 1} \frac 1{\omega_k} = \frac {\sum_k \prod_{j \neq k} \omega_j}{\prod_k \omega_k} = -\frac {s_a}{r_a}. We will show a recursive process that generates P a P_a , and then we will use that process to show inductively that r a = a 2 and s a = ( a 2 1 ) a 2 3 , (2) r_a = a^2 \quad \text{and} \quad s_a = -\frac {(a^2 - 1)a^2}3, \tag{2} from which (1) follows.

Let S a S_a denote the a a th spread polynomial, which is defined by S a ( x ) = 1 2 [ 1 T a ( 1 2 x ) ] , S_a(x) = \frac 12 [1 - T_a(1 - 2x)], where T a T_a is the a a th Chebyshev polynomial. One property of S a S_a is that S a ( sin 2 θ ) = sin 2 a θ S_a(\sin^2 \theta) = \sin^2 a\theta . Another is that S a S_a can be generated recursively by starting with S 1 = x S_1 = x and S 2 = 4 x 4 x 3 S_2 = 4x - 4x^3 and applying the rule S a + 1 ( x ) = 2 ( 1 2 x ) S a ( x ) S a 1 ( x ) + 2 x . (3) S_{a + 1}(x) = 2(1 - 2x)S_a(x) - S_{a - 1}(x) + 2x. \tag{3} Notice that S a ( x ) = 0 S_a(x) = 0 for x = 0 , ω 1 , ω 2 , , ω a 1 x = 0, \omega_1, \omega_2, \dots, \omega_{a - 1} . This means that 0 , ω 1 , ω 2 , , ω a 1 0, \omega_1, \omega_2, \dots, \omega_{a - 1} are exactly the roots of S a S_a , or equivalently, ω 1 , ω 2 , , ω a 1 \omega_1, \omega_2, \dots, \omega_{a - 1} are exactly the roots of S a ( x ) / x S_a(x)/x . Thus we have shown P a ( x ) = S a ( x ) x . P_a(x) = \frac {S_a(x)}x.

Now we will show by induction that (2) holds for all a 1 a \geq 1 . When we generate P a P_a for a = 1 a = 1 and a = 2 a = 2 , we see P 1 ( x ) = 1 + 0 x and P 2 ( x ) = 4 4 x , P_1(x) = 1 + 0x \quad \text{and} \quad P_2(x) = 4 - 4x, and we can verify directly that (2) holds. Fix b 2 b \geq 2 and find P b P_b and P b 1 P_{b - 1} . Extract the coefficients r b r_b , s b s_b , r b 1 r_{b - 1} , and s b 1 s_{b - 1} and suppose that (2) holds when a = b a = b and a = b 1 a = b - 1 . By (3), P b + 1 ( x ) = S b + 1 ( x ) x = 2 ( 1 2 x ) S b ( x ) x S b 1 ( x ) x + 2 = 2 ( 1 2 x ) P b ( x ) P b 1 ( x ) + 2. P_{b + 1}(x) = \frac {S_{b + 1}(x)}x = 2(1 - 2x) \frac {S_b(x)}x - \frac {S_{b - 1}(x)}x + 2 = 2(1 - 2x) P_b(x) - P_{b - 1}(x) + 2. From this equation, we find the constant and linear coefficient of P b + 1 P_{b + 1} are r b + 1 = 2 r b r b 1 + 2 and s b + 1 = s b 1 2 ( 2 r b s b ) . r_{b + 1} = 2r_b - r_{b - 1} + 2 \quad \text{and} \quad s_{b + 1} = - s_{b - 1} - 2(2rb - s_b) . Applying (2) and simplifying, we obtain r b + 1 = ( b + 1 ) 2 and s b + 1 = [ ( b + 1 ) 2 1 ] ( b + 1 ) 2 3 . r_{b + 1} = (b + 1)^2 \quad \text{and} \quad s_{b + 1} = -\frac{[(b + 1)^2 - 1](b + 1)^2}3. Thus we have shown that (2) holds when a = b + 1 a = b + 1 . By induction, (2) holds for all a a , and this is the result that confirms the identity in (1).

Note: I found this proof of (1) (along with several others) at StackExchage .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...